Serous papillary cystadenofibroma of the fallopian tube: A case report and short review of literature - Yasmeen Khatib (Indian Journal of Pathology and Microbiology, 2015)
Serous papillary cystadenofibromas (SPCAFs) of the fallopian tube are very rare benign tumors of the female genital tract. They are usually asymptomatic and are found incidentally. Until now, only 18 cases of this tumor have been reported in the world literature. We report a case of SPCAF of the left fallopian tube in a 30-year-old female who presented with a large abdominal mass and pain. On computed tomography, a diagnosis of ovarian neoplasm was given. However, during surgery the tumor was found to arise from the fallopian tube and was treated with tubal cystectomy with sparing of the ovary. We present this unique case on account of its rarity, unusual presentation, and huge size along with a short review of literature.